2022
DOI: 10.3390/su142113819
|View full text |Cite
|
Sign up to set email alerts
|

Selected Economic Determinants of Labor Profitability in Family Farms in Poland in Relation to Economic Size

Abstract: Farms in Poland come in a wide variety of sizes, and the effect of farm size on the profitability of labor has not been sufficiently investigated. This paper takes a fresh look at the model for labor profitability determinants of family farms in Poland in relation to their economic size. The purpose of this paper is to analyze the factors that determine the labor profitability index in farms of various economic size classes (classes ES1–ES5). In the analysis of factors shaping the profitability of labor in fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 128 publications
1
9
0
1
Order By: Relevance
“…Omotilewa et al also have found that agricultural policy can promote the growth of agricultural productivity, agricultural commercialisation, and food security in Nigeria [45]. Kusz et al discussed the impact of macro factors and agricultural subsidies on the scale change of grain farms in Poland [46]. This is because geography and policy support may continue to influence the business decision-making behaviour of farmers in other nations, as evidenced by studies on the agricultural scale and efficacy of the dairy industry in Western Europe and the grape industry in Western Cape, South Africa [47].…”
Section: Discussionmentioning
confidence: 99%
“…Omotilewa et al also have found that agricultural policy can promote the growth of agricultural productivity, agricultural commercialisation, and food security in Nigeria [45]. Kusz et al discussed the impact of macro factors and agricultural subsidies on the scale change of grain farms in Poland [46]. This is because geography and policy support may continue to influence the business decision-making behaviour of farmers in other nations, as evidenced by studies on the agricultural scale and efficacy of the dairy industry in Western Europe and the grape industry in Western Cape, South Africa [47].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][35][36][37]. Notwithstanding, the economic, social and ecological benefits of family farms can also be disturbed by various influencing factors [6,7,[35][36][37]40,41]. For instance, mechanisms and tools of agricultural policy, agricultural mechanization, crop establishment, wage labor, quality capabilities of agricultural managers, level of internal management, rural financial credit system, satisfaction of social service demand, support for agricultural science and technology, and quality and safety of agricultural products, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, mechanisms and tools of agricultural policy, agricultural mechanization, crop establishment, wage labor, quality capabilities of agricultural managers, level of internal management, rural financial credit system, satisfaction of social service demand, support for agricultural science and technology, and quality and safety of agricultural products, etc. [40][41][42][43][44][45][46]. As it should be, objectively speaking, the development of family farms in different countries and regions at different stages of development is affected by natural, social, economic, cultural, technical and other factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ustalono, że województwo zachodniopomorskie, które przed 2004 rokiem było w grupie województw o najmniej efektywnej produckji zbóż, stało się efektywne pod tym względem w okresie kilkunastu lat. Mogło to wynikać z korzystnej struktury obszarowej gospodarstw, gdyż w większych gospodarstwach poziom korzystania z postępu oraz efektywność wykorzystania nakładów jest wyższa niż w mniejszych [Kusz i in. 2022].…”
Section: Opis Danychunclassified